Elucidating Halogen‐Assisted Self‐Assembly Enhanced Mechanochromic Aggregation‐Induced Emission. Issue 7 (28th April 2021) - Miao, Xinrui; Cai, Zhengkai; Li, Jinxing; Liu, Liqian; Wu, Juntian; Li, Bang; Ying, Lei; Silly, Fabien; Deng, Wenli; Cao, Yong
Abstract: We present a successful strategy to obtain a self‐assembled material stabilized by halogen bonding with enhanced mechanochromic aggregation‐induced emission (AIE). The meta ‐bromophenyl‐substituted tetraphenylethene fluorophore ( m ‐BrTBE) exhibits an emission which is more red‐shifted compared to the phenyl‐ring‐substituted tetraphenylethene fluorophore (TBE) in film. Remarkably, m ‐BrTBE molecules self‐assemble into uniform ball‐like aggregates with high photoluminescence quantum yield up to 85.3 %, which indicates that the molecular conformation and intermolecular interactions are different from those in the crystalline state. Based on single‐crystal analysis, scanning tunneling microscopic observations, and theoretical calculations, the unusual self‐assembly enhanced AIE behavior is attributed to the important effect of meta ‐bromide substituents which not only form intermolecular Br⋅⋅⋅π halogen bonding and H⋅⋅⋅Br hydrogen bonding interactions to block nonradiative relaxation pathways effectively but also promote radiative processes. Abstract : Seeing red : The meta ‐bromophenyl‐substituted tetraphenylethene fluorophore (m‐BrTBE) exhibits aggregation induced emission mechanochromic properties. m ‐BrTBE exhibits stronger red‐shifted emission in a thin film compared to in its crystal state. Remarkably, m ‐BrTBE molecules self‐assemble into uniform ball‐like aggregates with high photoluminescence quantum yield up to 85.3 % mainly resulting from the intermolecular Br ⋅⋅⋅ π halogen bonding.